Crossing borders, shaping politics: A study on the political interest of Chinese international student returnees of Eastern China - Ruining Jin; Boya Wu; Tam-Tri Le (PLoS ONE, 2025)
The political interest of highly educated returnees represents a significant force in shaping the political landscape and bridging cultural and political divides. Conducting Bayesian analysis aided by Markov Chain Monte Carlo (MCMC) algorithms on a sample of 1014 returnee participants, this research probed the influence of sociodemographic and socio-psychological factors on political interest of the Chinese international student returnee population. The findings reveal that education attainment, age, and individualistic values negatively correlate with political interest, while time spent abroad and the intention to emigrate positively affect returnees’ interest in politics.